2009
DOI: 10.1016/j.jpeds.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Diagnosis in Duchenne Muscular Dystrophy: Data from the Muscular Dystrophy Surveillance, Tracking, and Research Network (MD STARnet)

Abstract: There is a delay of about 2.5 years between onset of DMD symptoms and the time of definitive diagnosis, unchanged over the previous 2 decades. This delay results in lost opportunities for timely genetic counseling and initiation of corticosteroid treatment. We recommend checking creatine kinase early in the evaluation of boys with unexplained developmental delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
193
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(213 citation statements)
references
References 24 publications
14
193
0
6
Order By: Relevance
“…Glucocorticoid treatment prolongs ambulation and improves quality of life, and the current recommendation is to begin corticosteroid treatment when boys with DMD have stopped gaining motor milestones, but before their motor skills have begun to decline (Mendell, 2012;Bushby, 2010). The average age of diagnosis for DMD is currently 5 years of age (Ciafaloni, 2009), but the loss of motor skills may have already begun before this age. An earlier diagnosis could lead to better medical management for the child (Mendell, 2012).…”
Section: Nbs Is a Well-established Public Health Initiative With Strumentioning
confidence: 99%
“…Glucocorticoid treatment prolongs ambulation and improves quality of life, and the current recommendation is to begin corticosteroid treatment when boys with DMD have stopped gaining motor milestones, but before their motor skills have begun to decline (Mendell, 2012;Bushby, 2010). The average age of diagnosis for DMD is currently 5 years of age (Ciafaloni, 2009), but the loss of motor skills may have already begun before this age. An earlier diagnosis could lead to better medical management for the child (Mendell, 2012).…”
Section: Nbs Is a Well-established Public Health Initiative With Strumentioning
confidence: 99%
“…8 Historical studies suggest an average age of diagnosis of DMD of 5 years in the United States and Europe, this figure remaining relatively stable over 26 years. [9][10][11][12][13][14] Age of diagnosis in Australia has not been previously published. Ciafaloni et al 14 observed a 2.5 year delay between parents first noticing symptoms and ultimately receiving a DMD diagnosis for their child.…”
Section: Introductionmentioning
confidence: 99%
“…34 It is evident that the age at diagnosis over time in the UK population has not changed significantly in the last 20 years. 3 The reported incidence of 1:4046 for DMD in Wales for the birth cohort 1971-1986, 35 before the commencement of this screening programme, is higher than the incidence of 1:5136 in the Wales birth cohort 1990-2011. The avoidance of further affected boys in families where the first affected child is diagnosed early is an important consequence of screening, resulting in part from the deferral of future pregnancies when a child is found to have a serious illness and in part from parental decisions to use prenatal diagnostic testing to enable the selective termination of affected pregnancies.…”
Section: Discussionmentioning
confidence: 83%
“…1 The mean age for diagnosis has remained unchanged over many years at 4.5-5.5 years. [2][3][4][5] It is frequently reported that parents had sought medical advice before this (mean delay from presentation to diagnosis is about 2 years), 3 resulting in diagnostic delay and causing considerable anxiety and distress. 6,7 The development of blood spot CK assays gave the potential for newborn boys to be screened for DMD.…”
Section: Introductionmentioning
confidence: 99%